Une première approche de la reconstruction des principaux pôles internationaux de formation des scientifiques mexicains à partir de 1960 - Rocío Grediaga Kuri; Estela Maldonado Pérez (Les éditions de la Maison des sciences de l'Homme, 2012)
Understanding the risks and benefits of internationalizing higher education is a topic of growing importance in the Mexican government and academic community. Changes in public policy in Mexico have been happening in the past twenty years without diagnosis to get adequate information on the impact studies abroad have represented in the evolution of academic networks and their contribution to Mexican's insertion in the main current of Science. Using the National System of Researchers (SNI) data base, we had reconstructed the formative processes of the SNI's members, especially locating institutions and countries where they had obtained their PhD degree. After analyzing inflexions in public policy measures, we established three different periods to see potential changes in reference poles during time: 1) before 1984, date of implementation of SNI, which has been a major change in scientific economic and status reward system; 2) between 1985 and 1996, period characterized by a generalization of academic's merit pay programs within the higher education public institutions; 3) 1996 to date, when the Mexican government via the Education Ministry (SEP) and the National Council of Science and Technology (CONACYT) have given additional resources to improve degrees of the academics in Mexico. We observed wide variations in countries and institutions where graduate studies were done within the different disciplines and periods of study. So we sustain as hypothesis in competence if these inflexions in public policy towards science, technology and higher education could be a relevant factor to explain diversity through time and fields of study or if this diversity could be better understood by the disciplinary traditions' orientation to different research groups and institutions of reference. At the end we found that an explanation should consider the interaction of these two aspects, the weight of each will depend on the stage of development of the disciplinary community in different knowledge fields in Mexico.